A perforator from the ulnar artery and cutaneous nerve of the hypothenar area: An anatomical study for clinical application. Issue 1 (3rd August 2015) - Han, Hyun Ho; Choi, Yong Seong; Kim, In Beom; Kim, Sang Hyun; Jun, Young‐Joon
Abstract : Purpose: The hypothenar perforator flap is a recently introduced method for fingertip reconstruction, which offers excellent results but lacks adequate anatomic studies. The present study is aimed to clarify the anatomic characteristics of the hypothenar area to analyze the potential clinical application of sensate flaps and to access the reliability of hypothenar perforator arteries. Materials and Methods: A total of 26 amputated forearms were used, and a percentage scattergram using an x‐y ‐axis was created. The y ‐axis was a vertical line from the midpoint of pisiform base (0%) to the midvolar crease of the metacarpophalangeal joint (100%). The x ‐axis was a line perpendicular to the y ‐axis, and was quantified as a percentage value. We then studied the number of perforators, the diameter and length of the pedicle, and evaluated the differences between the zones and sexes. Results: A reliable region for the hypothenar perforator flap, including more than two perforator arteries with an average diameter of over 1 mm, was mapped as 5%–20% on the x ‐axis and 10%–50% on the y ‐axis. The nerves appeared to occur more densely than the arteries, with 5%–15% on the x ‐axis and 25%–60% on the y ‐axis. Conclusion: The most consistent area for sensate flap elevation was the region around 5%–15% on the x ‐axis and 25%–50% on the y ‐axis. We expect that our data concerning perforator artery and cutaneous nerve branches in the hypothenar area of the hand will aid in establishing appropriate clinical usage of the hypothenar perforator flap. © 2014 Wiley Periodicals, Inc. Microsurgery 37:49–56, 2017.